0
$\begingroup$

Consider the set of functions from some set X $\rightarrow$ X. The relation fRg is defined by $$g = a^{-1} \circ f \circ a$$ for some function $a$ that is bijective from X $\rightarrow$ X. I am wondering how to prove the equivalence relation, and to find the equivalence class for f(x) = x.

Reflexive: Look at $f(x) = a^{-1}(f(a(x)))$. Then take the bijective function $a(x) = x$, and clearly $f(x) = f(x)$ for all $x \in X$. So the relation is reflexive.

I'm having trouble proving the others. For example, with symmetry, I am unable to find a way to get from $g(x) = a^{-1}(f(a(x))) \Longrightarrow f(x) = a^{-1}(g(a(x)))$.

$\endgroup$
9
  • 1
    $\begingroup$ If $g = a^{-1}\circ f\circ a$, then $f = a\circ g\circ a^{-1}$. Can you prove transitivity? $\endgroup$ – amsmath Oct 6 '19 at 1:50
  • $\begingroup$ My current efforts with transitivity have left me stuck; assume two relations fRg and gRh. Then I can write $h = a^{-1} \circ g \circ a$. Then replace the $g$ in this equation to get $h = a^{-1} \circ a^{-1} \circ f \circ a \circ a$, which does not give the result I hoped for since the function $a$ is there two times. I feel like I'm misunderstanding something important $\endgroup$ – sjrr00 Oct 6 '19 at 2:10
  • 1
    $\begingroup$ Nope. The '$a$' connecting $h$ and $g$ might be another function than $a$, so you should give it another name, say $b$. Note furthermore that $(a\circ b)^{-1} = b^{-1}\circ a^{-1}$. $\endgroup$ – amsmath Oct 6 '19 at 2:11
  • $\begingroup$ oh gosh, thanks for pointing that out. Using the property that you told me, I was able to get $(a \circ b)^{-1} \circ f \circ ( a \circ b)$ which corresponds to the what the relation needs. $\endgroup$ – sjrr00 Oct 6 '19 at 2:33
  • 1
    $\begingroup$ If you put $b=a^{-1}$, then $f = b^{-1}\circ g\circ b$, as desired. ;-) $\endgroup$ – amsmath Oct 6 '19 at 2:42
0
$\begingroup$

Reflexive:$$ f=id f id^{-1} \implies fRf$$

Symmetric :$$f=a^{-1}ga \implies g=afa^{-1}$$

Transitive: $$f=a^{-1}ga$$, and $$g=b^{-1}hb$$ then $$f=a^{-1}b^{-1}hba = (ba)^{-1}h (ba)$$

$\endgroup$
1
  • $\begingroup$ We got all that in the comments already. $\endgroup$ – amsmath Oct 6 '19 at 2:37

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.